(D^2 - D'^2 - 3D + 3D')z = xy
Given equation is (D^2 - D'^2 - 3D + 3D')z = xy
Auxilliary equation is "m^2-1-3m+3 = 0"
"m=1,2"
Then, "z = f_1(x+y)+f_2(3x+y)"
C.F. "\\frac{1}{(D^2 - D'^2 - 3D + 3D')}xy = \\frac{1}{3D'(1+\\frac{D^2 - D'^2 - 3D}{3D'})}xy"
"\\frac{1}{3D'}(1+\\frac{D^2 - D'^2 - 3D}{3D'})^{-1}xy =\\frac{1}{3D'}(1-\\frac{D^2 - D'^2 - 3D}{3D'})xy"
"= \\frac{1}{3D'}[xy-\\frac{1}{3D'}(-3y)] =\\frac{1}{3D'}( xy+\\frac{y^2}{2}) = \\frac{1}{6}xy^2 + \\frac{1}{18}y^3"
So, the solution of the equation is "z = f_1(x+y)+f_2(3x+y)+\\frac{1}{6}xy^2 + \\frac{1}{18}y^3"
Comments
Leave a comment